THU0189 One-year treatment retention after a nationwide non-medical switch from originator to biosimilar etanercept in 2, 061 patients with inflammatory arthritis followed in the danbio registry. (12th June 2018) - Glintborg, B.; Sørensen, I.J.; Omerovic, E.; Mehnert, F.; Manilo, N.; Danebod, K.; Jensen, D.V.; Nordin, H.; Loft, A.G.; Hendricks, O.; Chrysidis, S.; Andersen, B.L.; et al.
Abstract : Background: In Denmark, rheumatoid arthritis(RA), psoriatic arthritis(PsA) and axial spondyloarthritis(AxSpA) patients (pts) treated with originator etanercept (ETA) 50 mg SC conducted a mandatory non-medical switch to biosimilar Etanercept (SB4) in April 2016 ( switchers). Pts treated with 25 mg ETA or 50 mg powder solution were not mandated to switch ( non-switchers). Objectives: To characterise switchers and non-switchers, and to compare 1 year treatment retention in switchers with non-switchers and a historic cohort of ETA treated pts. Methods: Pt data were retrieved from the DANBIO registry and national registries. We applied Chi-square/Mann-Whitney for comparisons and Kaplan-Meier/Cox regression analyses (crude, adjusted for gender/age/MTX/remission/comorbidities/ETA-start-year) for drug retention. The historic cohort encompassed pts treated with ETA by Jan 1st 2015. Results: Of 2, 061 ETA treated pts by April 2016, 79% switched to SB4 (933RA/351PsA/337AxSpA), whereas 21% (286RA/56PsA/98AxSpA) continued ETA. In RA, compared to switchers, non-switchers more often received 25 mg ETA, had higher disease activity and HAQ (table 1). Similar patterns were seen for PsA and AxSpA. Median(IQR) follow-up was 383(314–414)days. In all 3 cohorts, withdrawals were mainly due to lack of effect. Retention rate was lowest in non-switchers (figure 1). 1 year adjusted rates were 83% (95% CI 79–87) in switchers, 77%( 72–82 in non-switchers and 90%( 88–92 in historic cohort. Pts not in remission had poorer retention than pts in remission both in switchers (hazard ratio 1.7 (1.3–2.2) and non-switchers (2.4 (1.7–3.6)). Numbers are medians (IQR) unless otherwise stated. * DAS28 <2.6 (RA, PsA), ASDAS <1.3 (AxSpA) Conclusions: Of >2000 ETA treated pts, ≈80% switched to SB4. Non-switchers had higher disease activity and more often received 25 mg ETA. Switchers had poorer retention rate than a historic ETA-cohort, but better than non-switchers. Withdrawal was most common in pts not in remission. These real-world data indicate that a switching-to-biosimilar option facilitated clinical decision making in standard care, leading to withdrawal from ineffective therapy in both switchers and non-switchers. Acknowledgements: Partly sponsered by Biogen Disclosure of Interest: B. Glintborg Grant/research support from: Abbvie, Biogen, Pfizer, I. Sørensen: None declared, E. Omerovic: None declared, F. Mehnert: None declared, N. Manilo: None declared, K. Danebod: None declared, D. Jensen: None declared, H. Nordin: None declared, A. G. Loft Grant/research support from: AbbVie, MSD, Novartis, Pfizer, Roche, UCB, O. Hendricks Grant/research support from:: Abbvie, Roche, Novartis, S. Chrysidis: None declared, B. Andersen: None declared, J. Raun: None declared, H. Lindegaard: None declared, J. Espesen: None declared, S. Jakobsen: None declared, I. M. Hansen Grant/research support from: Roche, E. Dalsgaard: None declared, D. Pedersen: None declared, S. Kristensen: None declared, A. Linauskas: None declared, L. Andersen: None declared, J. Grydehøj: None declared, N. Krogh: None declared, M. Hetland Grant/research support from: Abbvie, Biogen, BMS, CellTrion, MSD, Novartis, Orion, Pfizer, Samsung, UCB